1983
DOI: 10.1021/bi00276a032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of histidine and methionine residues in the active site of the human uterine progesterone receptor with the affinity labels 11.alpha.- and 16.alpha.-(bromoacetoxy)progesterone

Abstract: The affinity labels 11 alpha- and 16 alpha-(bromo[2'-3H]acetoxy)progesterone (BAP) react covalently with amino acids present in the progesterone binding site of the human uterine progesterone receptor. Hydrolysis of the affinity labeled receptor followed by separation and analysis of the amino acid products demonstrated the sites of affinity labeling. The 11 alpha-BAP alkylates the 1-position of a histidine residue. The 16 alpha-BAP alkylates the 3-position of histidine, and a methionine residue. Affinity labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Second, binding was irreversible since dihydrotestosterone was not capable of exchanging with the affinity label after it was bound to the receptor. Covalent binding of testosterone 17/3-bromoacetate to the androgen receptor (Mainwaring & Johnson, 1980) and 1 laand 16abromoacetate derivatives of progesterone to the progesterone receptor (Holmes & Smith, 1983) also has been described recently.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Second, binding was irreversible since dihydrotestosterone was not capable of exchanging with the affinity label after it was bound to the receptor. Covalent binding of testosterone 17/3-bromoacetate to the androgen receptor (Mainwaring & Johnson, 1980) and 1 laand 16abromoacetate derivatives of progesterone to the progesterone receptor (Holmes & Smith, 1983) also has been described recently.…”
Section: Discussionmentioning
confidence: 96%
“…As shown in this study, dihydrotestosterone 17/8-bromoacetate appears to bind with the active binding site of the androgen receptor in a structure-specific manner. Specific binding of 1 laand 16a-(bromoacetoxy) progesterone, dexamethasone 21-mesylate, and tamoxifen aziridine to progesterone (Holmes & Smith, 1983), glucocorticoid (Simons et al, 1983;Weisz et al, 1983), and estrogen receptors (Katzenellenbogen et al, 1983), respectively, has been reported. Both dihydrotestosterone 17/3-bromoacetate and dexamethasone 21-mesylate have approximately '/^th the affinity for receptors as compared to their respective precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This peptide segment would therefore delineate a large part of the site around the steroid label, provided that the two labeled residues belong to the same subunit and that affinity labeling reagents retain the same position in the binding site as unmodified ligands. However, the presence of a bromoacetate substituent at the C-17 position, which confers a low affinity to the nucleophilic DHT reagent, as well as the possible rotation of the bromoacetoxy group around the 17,20 single bond (Holmes & Smith, 1983) can both facilitate a shift of the entire reagent toward the nearest reactive residue available around the site. On the other hand, the ability of human SHBG to accomodate the three DHT, T, and E2 ligands as well as 2-methoxy-E2 (Dunn et al, 1980) or 2-iodo-E2 (Fernlund & Gershagen, 1990), each with different A-ring structures, suggests a loose interaction with the peptide segments corresponding to rings A or B. Conversely, the structures of rings C and D, which are common to the five latter ligands, could be expected to correspond to a more selective interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the thioether bond of methionine is usually considered to be of low reactivity, a number of pieces of experimental evidence from affinity labelling experiments, suggest that in several enzymes may act as a reactive nucleophile. For example, a methionine residue is modified in isocitrate dehydrogenase [44], in human uterine progesterone receptor [45], and d ‐amino acid oxidase [46,47] by reaction with iodoacetate, 16α‐(bromoacetoxy)progesterone and O‐ (2,4‐dinitrophenyl)hydroxylamine, respectively.…”
Section: Identification Of Gst I Residue Modified By Sdtgmentioning
confidence: 99%